DeBakey type I acute aortic dissection with circular separation of the intima of the brachiocephalic trunk - S. Yu. Boldyrev; V. N. Suslova; V. A. Pekhterev; K. O. Barbukhatti; V. A. Porkhanov (Вестник хирургии имени И.И. Грекова)
Surgical treatment of DeBakey type I acute aortic dissection is still accompanied by a relatively high mortality rate and complications. Organ malperfusion makes a serious contribution to the structure of mortality in the surgical treatment of patients with acute aortic dissection. At the same time, the spread of dissection to the brachiocephalic arteries is observed in 15–40 % of cases. Some of these patients suffer a transient ischemic attack or stroke in the preoperative period, which significantly aggravates the patient’s condition. We present a clinical case of successful surgical treatment of a patient with DeBakey type I acute aortic dissection, in whom intraoperatively a circular separation of intima from the mouth of the brachiocephalic trunk with its invagination into the lumen of the aortic arch was detected. The patient underwent supracoronary prosthetics of the ascending aorta with incomplete prosthetics of the entire arch and prosthetics of the brachiocephalic trunk. This clinical case demonstrates a variant of the natural course of DeBakey type I acute aortic dissection with a complete separation of intima, which requires active surgical tactics. Currently, due to the lack of sufficient clinical experience in the treatment of patients with such a diagnosis, the question of choosing the optimal surgical tactics remains open.